Evaluation of Anti‐Alzheimer Activity of Synthetic Coumarins by Combination of in Vitro and in Silico Approaches. Issue 12 (14th November 2022) - Erdogan Orhan, Ilkay; Deniz, F. Sezer Senol; Salmas, Ramin Ekhteiari; Irmak, Sule; Acar, Ozden Ozgun; Turgut, Gurbet Celik; Sen, Alaattin; Zbancioc, Ana‐Maria; Luca, Simon Vlad; Skiba, Adrianna; Skalicka‐Woźniak, Krystyna; Tataringa, Gabriela
Abstract: Series of synthetic coumarin derivatives (1‐16 ) were tested against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), two enzymes linked to the pathology of Alzheimer's disease (AD). Compound 16 was the most active AChE inhibitor with IC50 32.23±2.91 μM, while the reference (galantamine) had IC50 =1.85±0.12 μM. Compounds 9 (IC50 75.14±1.82 μM), 13 (IC50 =16.14±0.43 μM), were determined to be stronger BChE inhibitors than the reference galantamine (IC50 =93.53±2.23 μM). The IC50 value of compound 16 for BChE inhibition (IC50 =126.56±11.96 μM) was slightly higher than galantamine. The atomic interactions between the ligands and the key amino acids inside the binding cavities were simulated to determine their ligand‐binding positions and free energies. The three inhibitory coumarins (9, 13, 16 ) were next tested for their effects on the genes associated with AD using human neuroblastoma (SH‐SY5Y) cell lines. Our data indicate that they could be considered for further evaluation as new anti‐Alzheimer drug candidates. Abstract :